BIOGRAFI H. SAKTI ALAM WATIR (1982-2018) - Deki Syaputra, Massanta, (Universitas Batanghari Jambi, 2020)
AbstractThe press is a social institution that carries out journalistic activities that provide information to the public using print media, electronic media and all types of available channels. Throughout history, the press in Indonesia has given birth to figures who play a role in providing information to the public, both at national and regional levels, so that it has become an academic concern to get to know these figures through biographical research. Some figures that have been written by researchers include Ashadi Siregar (2014), Jakob Oetama (2005) and Muktar Lubis (2011) as well as a series of other names written by Soebagijo IN about the profile of national reporters in his book titled Jagat Journalist Indonesia. Besides that, there are also a series of names of regional press figures in Indonesia, including Ani Idrus (Medan), Hasril Chaniago (West Sumatra), Hasyim Afwan (Java) and a series of other names that have carved the history of the press in a number of regions in Indonesia. Likewise with the press in Jambi, the figure of a journalist named H. Syamsulwatir Mdikenal known as the pioneer.Keywords: Biography, Career Journey.AbstrakPers merupakan lembaga sosial yang melaksanakan aktivitas jurnalistik yang memberikan informasi kepada masyarakat dengan menggunakan media cetak, media elektronik dan segala jenis saluran yang tersedia. Sepanjang sejarah, pers di Indonesia telah melahirkan tokoh yang berperan dalam memberikan informasi kepada masyarakat, baik di tingkat nasional maupun daerah, sehingga menjadi perhatian akademisi untuk mengenal tokoh-tokoh tersebut melalui penelitian biografi. Beberapa tokoh yang telah ditulis oleh peneliti diantaranya Ashadi Siregar (2014), Jakob Oetama (2005) dan Muktar Lubis (2011) serta sederetan nama lainnya yang ditulis oleh Soebagijo IN tentang profil para pelapor persnasional dalam bukunya yang berjudul Jagat Wartawan Indonesia. Disamping itu, terdapat juga sederetan nama tokoh pers daerah di Indonesia antara lain Ani Idrus (Medan), Hasril Chaniago (Sumatera Barat), Hasyim Afwan (Jawa) dan sederetan nama lainnya yang telah mengukir sejarah pers disejumlah daerah di Indoneisa. Begitu juga halnya dengan pers di Jambi, sosok wartawan yang bernama H. Syamsulwatir Mdikenal dengan sebutan sang pionir.Kata kunci: Biografi, Perjalanan Karir